PENGGUNAAN MEDIA LKS UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI PESERTA DIDIK - kiki fidya wati (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2020)
This research aims to improve Biology learning outcomes about Virus material using student worksheet media. This class action research consists of two cycles. Each cycle consists of 4 stages, namely: planning, implementation, observation and reflection. The subjects of this study were students of class X MIPA 2 MAN 1 Jombang. The data obtained in the form of results of daily tests of Virus material analyzed in quantitative descriptive. The analysis showed that student learning outcomes in the first cycle amounted to 71.88% and in the second cycle increased 9.37% to 81.25%. Learning by using media LKS that has been done can improve student learning outcomes in class X MIPA 2 MAN 1 Jombang on virus material. This learning media can be used as an alternative biological learning media, especially for Virus material. Keywords: Media, student worksheet, Learning Outcomes, Biology, PTK